Unveiling the Vibrant Tapestry: Brazilian Female Voices in Visual Poetry on Instagram - Rodrigues dos Santos, Ana Amélia (Journal of Digital Sociohumanities, 2024)
This article explores the presence of Brazilian women artists in visual poetry on Instagram. It highlights the historical decline in recognition of women artists and the perpetuation of stereotypes that undermine their work. The article also discusses the ongoing struggle faced by female writers for recognition in the literary field. It challenges the notion that women, especially those from diverse backgrounds, are not prolific producers of poetry. The author focuses on the work of Brazilian artist Heloísa Marques as an illustrative example. Marques, an architect and visual artist, uses embroidery and collage techniques in her visual poetic compositions. The article examines her background, techniques, approach to language, and the reception of her work on Instagram. It emphasizes how social media platforms like Instagram have become spaces where women can share their work and regain recognition as poets and artists. The article sheds light on Marques's artistic contributions and the broader presence of women in visual poetry on Instagram.